Weight stigma and fat phobia in Poland – attitudes towards people living with obesity and the level of knowledge about obesity among the social media internet respondents and medical professionals - Świder, Karolina; Baska, Alicja; Babicki, Mateusz; Mastalerz-Migas, Agnieszka; Kłoda, Karolina (Frontiers in Nutrition, 2023)
Obesity often subjects individuals to stigmatization, impacting self-esteem, contributing to depression, social isolation, and even exacerbating weight gain. Our research aimed to evaluate weight stigma, fat phobia, their expressions, and obesity-related knowledge among social media internet respondents and medical practitioners in Poland. Conducted through Computer-Assisted Web Interview (CAWI), our study employed the Fat Phobia Scale (FPS) and tailored questions, analyzing 1705 questionnaires. The respondents averaged a score of 3.60 ± 0.62 on the FPS. Interestingly, men exhibited higher stigma levels than women. Variables like BMI, residency, and interactions with people having obesity did not significantly impact stigma levels. Approximately 74.0% of respondents found individuals with obesity less attractive than those with normal weight, while 32.2% identified obesity as a cause of shame. Only 69.1% were aware of the BMI-based obesity diagnosis criterion. Given limited knowledge of Poland's weight stigma landscape, our research yields crucial insights for shaping social campaigns and enhancing educational initiatives in obesity management for healthcare professionals. Further studies will be instrumental in addressing patient and practitioner needs effectively.